Boys, Childhood Domestic Abuse and Gang Involvement : Violence at Home, Violence On-Road - Levell, Jade (Book collections on Project MUSE., 2022)
Previously overlooked in domestic violence and abuse policy and practice, Jade Levell offers radical insights into the lives of young boys in DVA-affected households. Showing how boys in this context navigate their journey to manhood, including gang involvement, the book makes practice recommendations for supporting these 'hidden victims'.